Reaction of passion fruit species to fusarium oxysporum f. sp. passiflorae and quality of fruit under different crop systems - Melo, Naama Jessica de Assis (Universidade Federal Rural do Semi-Árido, 2019)
Brazil is the main producer of yellow passion fruit (Passiflora edulis) in the world. One of the main diseases that reduce its production is fusariosis, caused by the fungus Fusarium oxysporum f. sp. passiflorae (FOP). The practice of grafting with resistant species is used to provide resistance to pests and diseases, such as fusariosis. One of these species is the P. cincinnata, used in much of the Northeastern region of Brazil. The objective of this work was to characterize the pathogenicity of different isolates of FOP in P. edulis and P. cincinnata in order to identify their potential for use in areas with a history of the disease and to verify postharvest quality of fruits of P. edulis collected inmature and mature in four areas with different forms of cultivation (conventional with and without grafting and organic with grafting). In the first experiment, thirteen isolates of the fungus were used and the inoculums produced at a concentration of 106 CFU mL-1. The seedlings of P. edulis and P. cincinnata were produced in coconut fiber and, 45 days after sowing, the root system was then immersed for five minutes in the conidial suspension before being replanted in the 770 mL pots. In the experiment ten replicates were used, for each species, each isolate and for the control group. Seedlings were evaluated daily from the second day after inoculation (DAI) until 90 DAI. After, a second experiment was installed in a completely randomized design, in a 4 x 2 factorial scheme, with five replicates of four fruits each. The first factor was the different collection sites with their cultivation systems and the second factor was the maturity stage. The fruits were harvested, selected and submitted to physical, physical-chemical and chemical analysis, bioactive compounds and antioxidant activity. All isolates were pathogenic in both Passiflora species, however incidence, severity and mortality were higher in P. edulis. There was a statistically significant difference for the incubation period of the FOP 23 and 57 isolates, being superior for P. edulis. Fruit weight, length, width and firmness were superior in fruits from conventional without grafting system, however fruit yield was inferior. Soluble solids, pH, reducing sugars and total soluble sugars were superior in fruits from collection sites with the use of grafting. Bioactive compounds and antioxidant activity were similar between the fruits from different collection sites
Keywords: Compostos bioativos; Fusariose; Passiflora cincinnata; Passiflora edulis; Patogenicidade; Bioactive compounds; Fusariosis; Passiflora cincinnata; Passiflora edulis; Pathogenicity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA